2016
DOI: 10.1051/0004-6361/201424149
|View full text |Cite
|
Sign up to set email alerts
|

A submillimetre search for pre- and proto-brown dwarfs in Chamaeleon II

Abstract: Context. The Chamaeleon II molecular cloud is an active star-forming region that offers an excellent opportunity to study the formation of brown dwarfs in the southern hemisphere. Aims. Our aims are to identify a population of pre-and proto-brown dwarfs (5σ mass limit threshold of ∼0.015 M ) and provide information on the formation mechanisms of substellar objects. Methods. We performed high sensitivity observations at 870 µm using the LABOCA bolometer at the APEX telescope towards an active star-forming regio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…So far, the only confirmed pre-BD is Oph B-11 (André et al 2012) and there are pre-BD candidates both in Taurus (Palau et al 2012;Tokuda et al 2019) and Barnard 30 (Huélamo et al 2017;Barrado et al 2018). Regarding proto-BDs, one excellent Class 0/I candidate has been identified in Perseus (Palau et al 2014) and other candidates are proposed in Taurus (Apai et al 2005;Barrado et al 2009;Palau et al 2012;Morata et al 2015;Dang-Duc et al 2016), Chamaeleon II (de Gregorio-Monsalvo et al 2016), Ophiuchus (Whelan et al 2018;Riaz et al 2018;Kawabe et al 2018), Serpens (Riaz et al 2016(Riaz et al , 2018, and σ Orionis (Riaz et al 2015(Riaz et al , 2017(Riaz et al , 2019, although many of these may also be more evolved Class I objects. Finally, the search and study of very low luminosity objects (VeLLOs) have revealed sources that show proto-BD characteristics (Bourke et al 2006;Lee et al 2009Lee et al , 2013Lee et al , 2018Kauffmann et al 2011;Kim et al 2019; also see the references in Table 4 of Palau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So far, the only confirmed pre-BD is Oph B-11 (André et al 2012) and there are pre-BD candidates both in Taurus (Palau et al 2012;Tokuda et al 2019) and Barnard 30 (Huélamo et al 2017;Barrado et al 2018). Regarding proto-BDs, one excellent Class 0/I candidate has been identified in Perseus (Palau et al 2014) and other candidates are proposed in Taurus (Apai et al 2005;Barrado et al 2009;Palau et al 2012;Morata et al 2015;Dang-Duc et al 2016), Chamaeleon II (de Gregorio-Monsalvo et al 2016), Ophiuchus (Whelan et al 2018;Riaz et al 2018;Kawabe et al 2018), Serpens (Riaz et al 2016(Riaz et al , 2018, and σ Orionis (Riaz et al 2015(Riaz et al , 2017(Riaz et al , 2019, although many of these may also be more evolved Class I objects. Finally, the search and study of very low luminosity objects (VeLLOs) have revealed sources that show proto-BD characteristics (Bourke et al 2006;Lee et al 2009Lee et al , 2013Lee et al , 2018Kauffmann et al 2011;Kim et al 2019; also see the references in Table 4 of Palau et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We can compare our results in B30 with those from two regions with very different properties: Chamaeleon II (Cha II, see de Gregorio-Monsalvo et al 2016) and the B213-L1495 clouds in Taurus (B213 hereafter Palau et al 2012;Morata et al 2015). Unlike B30, these are low-mass star forming regions that lack massive stars, and therefore do not suffer from the strong and ionizing winds associated to hot, massive objects.…”
Section: General Discussion and Conclusionmentioning
confidence: 78%
“…However, the envelope masses of FHCs are too large so it seems unlikely that they will remain substellar (see Table 4 in Palau et al 2014). Finally, observational studies using a multi-wavelength approach have provided several proto-BD candidates in different clouds and star forming regions Lee et al 2009Lee et al , 2013Kauffmann et al 2011;André et al 2012;Palau et al 2012Palau et al , 2014Morata et al 2015;Liu et al 2016;Riaz et al 2016;de Gregorio-Monsalvo et al 2016;Huélamo et al 2017). Despite these efforts, the number of proto-BD candidates is still very small and the characterization incomplete.…”
Section: Arxiv:171206399v1 [Astro-phsr] 18 Dec 2017mentioning
confidence: 99%
“…It may be possible that BDs form from core collapse, similar to higher-mass stars (see, e.g., André et al 2014; Riaz et al 2014;Lomax et al 2015). However, their masses are below or close to the Jeans mass in star-forming regions (e.g., Palau et al 2014;de Gregorio-Monsalvo et al 2016). Another formation mechanism may be the gravitational fragmentation of circumstellar disks, and numerical simulations suggest that this is indeed possible (e.g., Stamatellos & Whitworth 2009a, 2009bTsukamoto et al 2013;Forgan et al 2015;Dong et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It may be possible that brown dwarfs form from core collapse, similar to higher-mass stars (see, e.g., André et al 2014;Riaz et al 2014;Lomax et al 2015). However, their masses are below or close to the Jeans mass in star forming regions (e.g., Palau et al 2014;de Gregorio-Monsalvo et al 2016).…”
Section: Introductionmentioning
confidence: 99%